Antiproliferative activity of ruthenium complex II against human cancer cell in vitro - Mohamed Saadh (Pensoft Publishers, 2023)
Despite significant advancements in cancer treatment, there is a constant need for new and effective therapeutic options. One such potential weapon in the fight against cancer is ruthenium complex II. In this article, we synthesized, characterized, and studied the activity of dithiocyanato-N-bis[8-(diphenylphosphino)quinoline]ruthenium (II) [Ru(N-P)2(NCS)2] against MCF-7 human adenocarcinoma cells and the MRC-5 cell lines from fetal lung fibroblast-like cells as normal cells, as well as the mechanisms of action and selectivity. This study demonstrated that [Ru(N-P)2(NCS)2] has cytotoxic activity against MCF-7 with IC50 values of 7.56 µg/ml and cytotoxic activity against MRC-5 cell lines with IC50 values of 576.6 µg/ml. [Ru(N-P)2(NCS)2] showed more selective cytotoxic activity against MCF-7 cancer cell lines than MRC-5 normal cell lines. . This study demonstrated the potent apoptotic activity of ruthenium complex II by determining the activation of caspase-3, highlighting its potential as a therapeutic agent in cancer treatment. The [Ru(N-P)2(NCS)2] is considered promising for researchers investigating putative biological activities, particularly antitumor and immune-related activity.